Swimming Nymphs: A New Interpretation of the B side of the Lerici-Marescotti Amphora - Corso, Antonio (Actual Problems of Theory and History of Art, 2023)
The paper focuses on the amphora of the Attic Priam Painter dated around 510 B.C., found in Etruria, now kept in Rome at Museo di Villa Giulia. On the A side, Dionysus sits under a canopy of fruit-bearing vines while Satyrs pluck grapes in the surroundings of very luxuriant vegetation. On the B side, seven young dark-skinned nude girls or nymphs are either swimming or about to swim in the open sea, leaving their garments and accessories on boughs of two trees on the shore near a diving platform. The sides of the panel suggest a rocky setting, thus a remote grotto. The author suggests that this is the Cave of Nysa and that these are the nymphs who take care of Dionysus. Semantically, this scene reveals the notion of the erotic allure of the southern seas. Artistically, this may be the first surviving example of the indication of the horizon line between sea and sky.